Physiological demands across exercise intensity domains in rowing: implications of weight category and sex differences - Rios, M.; Cardoso, R.; Monteiro, A. S.; Vilas-Boas, J. P.; Fernandes, R. J. (Sports, 2025)
We examined the physiological demands of trained rowers across four exercise intensity domains (considering the effects of weight category and sex). Twenty-four trained rowers (12 lightweight and 12 heavyweight) performed 7 × 3 min incremental bouts on a Concept2 rowing ergometer (30 W power increases and 60 s rest intervals). Performance, cardiorespiratory and metabolic responses were continuously assessed throughout the experimental protocol to characterize internal load across progressive exercise intensities. Statistical analyses included a repeated measures ANOVA test and independent t-tests (p = 0.05). Heavyweight rowers exhibited greater absolute anaerobic energy production in the severe domain (41.25 ± 10.39 vs. 32.54 ± 5.92 kJ) (p = 0.02), higher peak metabolic power (up to 1.57 ± 0.30 vs. 1.48 ± 0.30 kW) (p = 0.001) and greater total energy expenditure (up to 277.52 ± 51.23 vs. 266.69 ± 51.59 kJ) (p = 0.001) than lightweight rowers, whereas the latter showed comparable relative cardiorespiratory responses to heavyweights. With respect to sex differences, males demonstrated higher oxygen uptake (from ~43-59 vs. ~34-48 mL·kg-1·min-1) (p = 0.001), ventilation (from ~78-146 vs. ~49-99 L·min-1) (p = 0.001), metabolic power (from ~1.1-1.7 vs. ~0.7-1.0 kW) (p = 0.001) and energy expenditure (from ~193-305 vs. ~119-209 kJ) (p = 0.001) across all intensity domains. However, blood lactate levels and anaerobic energy contributions were similar between sexes. These findings demonstrated that domain-based physiological profiling effectively differentiates internal responses among rowers by weight category and sex. Heavyweights showed greater absolute energy output, while lightweights demonstrated higher metabolic efficiency. Males had elevated cardiorespiratory and metabolic values, but relative bioenergetic responses were similar across groups. These findings support individualized training based on physiological profiles.